Delphinidin, One of the Major Anthocyanidins, Prevents Bone Loss through the Inhibition of Excessive Osteoclastogenesis in Osteoporosis Model Mice - Moriwaki, Sawako; Suzuki, Keiko; Muramatsu, Masashi; Nomura, Atsushi; Inoue, Fumihide; Into, Takeshi; Yoshiko, Yuji; Niida, Shumpei (PloS one, 2014)
Anthocyanins, one of the flavonoid subtypes, are a large family of water-soluble phytopigments and have a wide range of health-promoting benefits. Recently, an anthocyanin-rich compound from blueberries was reported to possess protective property against bone loss in ovariectomized (OVX) animal models. However, the active ingredients in the anthocyanin compound have not been identified. Here we show that delphinidin, one of the major anthocyanidins in berries, is a potent active ingredient in anti-osteoporotic bone resorption through the suppression of osteoclast formation. In vitro examinations revealed that delphinidin treatment markedly inhibited the differentiation of RAW264.7 cells into osteoclasts compared with other anthocyanidins, cyanidin and peonidin. Oral administration of delphinidin significantly prevented bone loss in both RANKL-induced osteoporosis model mice and OVX model mice. We further provide evidence that delphinidin suppressed the activity of NF-κB, c-fos, and Nfatc1, master transcriptional factors for osteoclastogenesis. These results strongly suggest that delphinidin is the most potent inhibitor of osteoclast differentiation and will be an effective agent for preventing bone loss in postmenopausal osteoporosis.